2010
DOI: 10.1007/s10482-010-9470-0
|View full text |Cite
|
Sign up to set email alerts
|

Antimycobacterial activity in vitro of pigments isolated from Antarctic bacteria

Abstract: In this study, we describe the antimycobacterial activity of two pigments, violacein, a purple violet pigment from Janthinobacterium sp. Ant5-2 (J-PVP), and flexirubin, a yellow-orange pigment from Flavobacterium sp. Ant342 (F-YOP). These pigments were isolated from bacterial strains found in the land-locked freshwater lakes of Schirmacher Oasis, East Antarctica. The minimum inhibitory concentrations (MICs) of these pigments for avirulent and virulent mycobacteria were determined by the microplate Alamar Blue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 46 publications
0
46
1
Order By: Relevance
“…Additionally these pigments may have clinical significance . Mojib et al, (2010) 15 showed that the pigments extracted from Janthinobacterium sp. and Flavobacterium sp.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally these pigments may have clinical significance . Mojib et al, (2010) 15 showed that the pigments extracted from Janthinobacterium sp. and Flavobacterium sp.…”
Section: Discussionmentioning
confidence: 99%
“…The alamarBlue assays were performed twice in triplicate. The nitrate reductase assay was performed to determine MICs of M. tuberculosis as previously described (36).…”
Section: Methodsmentioning
confidence: 99%
“…This pigment has the antitumor, antiparasitic, antiprotozoal, anti-cancer, antiviral, antibacterial and furthermore antioxidant activities (12,23,40). The antitumor mechanism of this pigment is still being studied, and it has been recently shown that the mentioned pigment activates the apoptosis in HL60 (leukemia) cell line and p38 MAPK through the activation of caspase-8 and transcription of NF-KB.…”
Section: Violaceinmentioning
confidence: 99%
“…and yellow-orange Flexirubin pigment gained from Flavobacterium sp. were studied by Mojib et al (12,40,42,47).…”
Section: Violaceinmentioning
confidence: 99%